PENINGKATAN HASIL BELAJAR PERPAJAKAN MELALUI MEDIA TAXI SNADERS PADA SISWA XI B SMK PL TARCISIUS 2 - Setyawan, Cornelius Hery (Dinamika Pendidikan, 2012)
Vocational School (SMK) is an educational institution to transfer knowledge about the tax. Unluckily, teaching learning process in delivering this material was monotonous, so it needed a medium called TAXI SNADERS. The objective of the study was to increase interest and learning outcomes taxation on Value Added Tax (VAT) and Sales of Luxury through a medium called TAXI SNADERS. The result of the study showed that there was improvement toward studentsâ interest for 14.5%. On the 1st cycle, studentsâ interest was only 67.25%, then it increased up to 81.75% on the 2nd cycle. Moreover, studentsâ learning outcomes also increased for 20% in post test. It was 67% on the 1st cycle and rose to 87% on the 2nd cycle.Â